2017
DOI: 10.1161/strokeaha.117.017290
|View full text |Cite
|
Sign up to set email alerts
|

No Racial Difference in Rehabilitation Therapy Across All Post-Acute Care Settings in the Year Following a Stroke

Abstract: Background and Purpose Black stroke survivors experience greater post-stroke disability than whites. Differences in post-acute rehabilitation may contribute to this disparity. Therefore, we estimated racial differences in rehabilitation therapy utilization, intensity and the number post-acute care settings in the first year after a stroke. Methods We used national Medicare data to study 186,168 elderly black and white patients hospitalized with a primary diagnosis of stroke in 2011. We tabulated the proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
2
27
0
3
Order By: Relevance
“…Compared with White stroke patients, Black stroke patients received more minutes of physical therapy, occupational therapy, and speech and language therapy. 16 One possible explanation for our findings may be the increased proportion of insured Black patients at 64.0% and even when uninsured at admission, and Black patients are more likely to eligible for indigent care or Medicaid before discharge as U.S. citizens. Insurance status is an important predictor of hospital disposition and access to specialized posthospital care.…”
Section: Discussionmentioning
confidence: 83%
“…Compared with White stroke patients, Black stroke patients received more minutes of physical therapy, occupational therapy, and speech and language therapy. 16 One possible explanation for our findings may be the increased proportion of insured Black patients at 64.0% and even when uninsured at admission, and Black patients are more likely to eligible for indigent care or Medicaid before discharge as U.S. citizens. Insurance status is an important predictor of hospital disposition and access to specialized posthospital care.…”
Section: Discussionmentioning
confidence: 83%
“…Stroke recovery can be a long and complex process, involving multiple domains of therapy (e.g., physical, occupational, communication, and cognitive) and occurs in inpatient rehabilitation facilities, skilled nursing facilities, and outpatient rehabilitation facilities. Benefits of stroke outpatient rehab have been determined to improve patient functional status, survival, cardiovascular risk profiles, and quality of life and reduce risks for recurrent strokes and psychological or stress disorders ( 3 , 4 , 8 , 9 ). Generally, stroke outpatient rehab participation is underutilized ( 3 , 8 ), which this study found to be true for all subgroups and states included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Third, alternative data sources, such as publically available administrative data, could be used to measure rehabilitation utilization. Medicare based data are being utilized in currently funded projects 13 ; however, stroke disparities are most pronounced in those less than 65 years of age and therefore, Medicare data does not capture the age range most critical for consideration of race-ethnic disparities in outcomes. Other potential data sources that could be utilized include the State Inpatient Databases, the National Inpatient Sample, or use of Optum®, a large data warehouse of privately insured patients supplemented with Medicaid mix data that can be purchased.…”
Section: Discussionmentioning
confidence: 99%